2021
DOI: 10.1200/jco.2021.39.15_suppl.tps12133
|View full text |Cite
|
Sign up to set email alerts
|

Olanzapine or dexamethasone, with 5-HT3 receptor antagonist and NK-1 receptor antagonist, to prevent nausea and vomiting induced by cisplatin-based doublet chemotherapy: A non-inferiority, prospective, multi-centered, randomized, controlled, phase III clinical trial.

Abstract: TPS12133 Background: Chemotherapy-induced nausea and vomiting (CINV) is a common side effect of cancer treatments, and dexamethasone offers an advantage over placebo for protection against chemotherapy-induced emesis in both acute and delayed phases. However, its side effects are diverse including moderate to severe insomnia, hyperglycemia, dyspepsia and so on, which are gathering increasing concerns. What’s more, dexamethasone is not applicable to all cancer patients. The incidence of diabetes mellitus varie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Some studies have found that reducing the dose of dexamethasone with the presence of a neurokinin-1 (NK1) receptor antagonist (RA) does not increase the incidence of CINV in patients treated with high emetic chemotherapy[28] [29]. Another study found that olanzapine was non-inferior to dexamethasone when they were combined with 5-hydroxytryptamine type 3 (5-HT3) RA and NK1 RA to prevent CINV induced by cisplatin-based chemotherapy [30]. For patients with colorectal carcinoma receiving moderate emetic chemotherapy (mFOLFOX6 regimen), aprepitant plus palonosetron was superior to dexamethasone plus palonosetron in preventing CINV [31].…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have found that reducing the dose of dexamethasone with the presence of a neurokinin-1 (NK1) receptor antagonist (RA) does not increase the incidence of CINV in patients treated with high emetic chemotherapy[28] [29]. Another study found that olanzapine was non-inferior to dexamethasone when they were combined with 5-hydroxytryptamine type 3 (5-HT3) RA and NK1 RA to prevent CINV induced by cisplatin-based chemotherapy [30]. For patients with colorectal carcinoma receiving moderate emetic chemotherapy (mFOLFOX6 regimen), aprepitant plus palonosetron was superior to dexamethasone plus palonosetron in preventing CINV [31].…”
Section: Discussionmentioning
confidence: 99%